Nanostructure selenium compounds as pseudocapacitive electrodes for high-performance asymmetric supercapacitor. Issue 1 (10th January 2018) - Ma, Guofu; Hua, Fengting; Sun, Kanjun; Fenga, Enke; Peng, Hui; Zhang, Zhiguo; Lei, Ziqiang
Abstract : The electrochemical performance of an energy conversion and storage device like the supercapacitor mainly depends on the microstructure and morphology of the electrodes. In this paper, to improve the capacitance performance of the supercapacitor, the all-pseudocapacitive electrodes of lamella-like Bi18 SeO29 /BiSe as the negative electrode and flower-like Co0.85 Se nanosheets as the positive electrode are synthesized by using a facile low-temperature one-step hydrothermal method. The microstructures and morphology of the electrode materials are carefully characterized, and the capacitance performances are also tested. The Bi18 SeO29 /BiSe and Co0.85 Se have high specific capacitance (471.3 F g –1 and 255 F g –1 at 0.5 A g –1 ), high conductivity, outstanding cycling stability, as well as good rate capability. The assembled asymmetric supercapacitor completely based on the pseudocapacitive electrodes exhibits outstanding cycling stability (about 93% capacitance retention after 5000 cycles). Moreover, the devices exhibit high energy density of 24.2 Wh kg –1 at a power density of 871.2 W kg –1 in the voltage window of 0–1.6 V with 2 M KOH solution.